Adipose Derived Mesenchymal Stem Cell Differentiation into Adipogenic and Osteogenic Stem Cells - Hassan IH El Sayyad1; Mohamed A Sobh2; Soad A Khalifa1; Omnia KR El-Sayyad (Studies on Stem Cells Research and Therapy - Peertechz Publications, 2016)
Objective: Lipoaspiration of human breast fats are important source of adipocyte stem cells (hAMSCs) which play a great role in regenerative medicine. The present study illustrates its capability of its transformation and characterization of adipocyte, osteogenic or chondrogenic cells. Methods and results: The hAMSCs were positive for CD13, CD29, CD105 and CD90 and negative CD34 and CD 14. The hAMSCs were cultured in adipogenic or osteogenic culture for 4,7,14 & 21 days. Gene expression for adipogenic (PCR of leptin, peroxisome proliferator-activated receptor-γ and lipoprotein lipase) and osteogenic (osteocalcin) cells were carried out. Biochemical assessments of adipogenic (lipoprotein lipase enzyme and glycerol-3-phosphate dehydrogenase) and osteogenic (alkaline phosphatase, B-galactosidase and calcium content) markers. Also, light and transmission electron microscopic investigation of adipocyte stem cell culture were investigated at 4,7,14 & 21 days in both two models. Adipocyte derived from hAMSCs displayed fi broblastic morphology and confl uency at 7 days and fl at-shape with positive oil red staining at 14 &21 days. At ultrastructural level, the adipocyte derived from hAMSCs exhibited ideal structure. Also, it showed adipogenic gene expression and  biochemical investigation. Similar was observed of its osteogenic affi nity of bone cells derived from hAMSCs. Conclusion: The authors concluded that adipocyte stem cells are capable of differentiating into adipocyte, osteoblast and chondroblast depending on the culture medium and are promising in regenerating medicine.